# 0.2 Equations and inequalities: solving linear equations  (Page 2/2)

 Page 2 / 2

## Method: solving equations

The general steps to solve equations are:

1. Expand (Remove) all brackets.
2. "Move" all terms with the variable to the left hand side of the equation, and all constant terms (the numbers) to the right hand side of the equals sign.Bearing in mind that the sign of the terms will change from ( $+$ ) to ( $-$ ) or vice versa, as they "cross over" the equals sign.
3. Group all like terms together and simplify as much as possible.
4. Factorise if necessary.
5. Find the solution.
6. Substitute solution into original equation to check answer.

Solve for $x$ : $4-x=4$

1. We are given $4-x=4$ and are required to solve for $x$ .

2. Since there are no brackets, we can start with grouping like terms and then simplifying.

3. $\begin{array}{ccc}\hfill 4-x& =& 4\hfill \\ \hfill -x& =& 4-4\phantom{\rule{1.em}{0ex}}\left(\mathrm{move}\mathrm{all}\mathrm{constant}\mathrm{terms}\left(\mathrm{numbers}\right)\mathrm{to}\mathrm{the}\mathrm{RHS}\left(\mathrm{right}\mathrm{hand}\mathrm{side}\right)\right)\hfill \\ \hfill -x& =& 0\phantom{\rule{1.em}{0ex}}\left(\mathrm{group}\mathrm{like}\mathrm{terms}\mathrm{together}\right)\hfill \\ \hfill -x& =& 0\phantom{\rule{1.em}{0ex}}\left(\mathrm{simplify}\mathrm{grouped}\mathrm{terms}\right)\hfill \\ \hfill -x& =& 0\hfill \\ \hfill \therefore \phantom{\rule{1.em}{0ex}}x& =& 0\hfill \end{array}$
4. Substitute solution into original equation:

$4-0=4$
$4=4$

Since both sides are equal, the answer is correct.

5. The solution of $4-x=4$ is $x=0$ .

Solve for $x$ : $4\left(2x-9\right)-4x=4-6x$

1. We are given $4\left(2x-9\right)-4x=4-6x$ and are required to solve for $x$ .

2. We start with expanding the brackets, then grouping like terms and then simplifying.

3. $\begin{array}{ccc}\hfill 4\left(2x-9\right)-4x& =& 4-6x\hfill \\ \hfill 8x-36-4x& =& 4-6x\phantom{\rule{1.em}{0ex}}\phantom{\rule{1.em}{0ex}}\left(\mathrm{expand}\mathrm{the}\mathrm{brackets}\right)\hfill \\ \hfill 8x-4x+6x& =& 4+36\phantom{\rule{1.em}{0ex}}\mathrm{move}\mathrm{all}\mathrm{terms}\mathrm{with}\mathrm{x}\mathrm{to}\mathrm{the}\mathrm{LHS}\hfill \\ \hfill \mathrm{and}\mathrm{all}\mathrm{constant}\mathrm{terms}\mathrm{to}\mathrm{the}\mathrm{RHS}\mathrm{of}\mathrm{the}=\\ \hfill \left(8x-4x+6x\right)& =& \left(4+36\right)\phantom{\rule{1.em}{0ex}}\left(\mathrm{group}\mathrm{like}\mathrm{terms}\mathrm{together}\right)\hfill \\ \hfill 10x& =& 40\phantom{\rule{1.em}{0ex}}\phantom{\rule{1.em}{0ex}}\phantom{\rule{1.em}{0ex}}\phantom{\rule{1.em}{0ex}}\left(\mathrm{simplify}\mathrm{grouped}\mathrm{terms}\right)\hfill \\ \hfill \frac{10}{10}x& =& \frac{40}{10}\phantom{\rule{1.em}{0ex}}\phantom{\rule{1.em}{0ex}}\phantom{\rule{1.em}{0ex}}\phantom{\rule{1.em}{0ex}}\left(\mathrm{divide}\mathrm{both}\mathrm{sides}\mathrm{by}10\right)\hfill \\ \hfill x& =& 4\hfill \end{array}$
4. Substitute solution into original equation:

$\begin{array}{ccc}\hfill 4\left(2\left(4\right)-9\right)-4\left(4\right)& =& 4-6\left(4\right)\hfill \\ \hfill 4\left(8-9\right)-16& =& 4-24\hfill \\ \hfill 4\left(-1\right)-16& =& -20\hfill \\ \hfill -4-16& =& -20\hfill \\ \hfill -20& =& -20\hfill \end{array}$

Since both sides are equal to $-20$ , the answer is correct.

5. The solution of $4\left(2x-9\right)-4x=4-6x$ is $x=4$ .

Solve for $x$ : $\frac{2-x}{3x+1}=2$

1. We are given $\frac{2-x}{3x+1}=2$ and are required to solve for $x$ .

2. Since there is a denominator of ( $3x+1$ ), we can start by multiplying both sides of the equation by ( $3x+1$ ). But because division by 0 is not permissible, there is a restriction on a value for x. ( $x\ne \frac{-1}{3}$ )

3. $\begin{array}{ccc}\hfill \frac{2-x}{3x+1}& =& 2\hfill \\ \hfill \left(2-x\right)& =& 2\left(3x+1\right)\hfill \\ \hfill 2-x& =& 6x+2\phantom{\rule{1.em}{0ex}}\left(\mathrm{remove}/\mathrm{expand}\mathrm{brackets}\right)\hfill \\ \hfill -x-6x& =& 2-2\phantom{\rule{1.em}{0ex}}\mathrm{move}\mathrm{all}\mathrm{terms}\mathrm{containing}\mathrm{x}\mathrm{to}\mathrm{the}\mathrm{LHS}\hfill \\ \hfill \mathrm{and}\mathrm{all}\mathrm{constant}\mathrm{terms}\left(\mathrm{numbers}\right)\mathrm{to}\mathrm{the}\mathrm{RHS}.\\ \hfill -7x& =& 0\phantom{\rule{1.em}{0ex}}\phantom{\rule{1.em}{0ex}}\phantom{\rule{1.em}{0ex}}\left(\mathrm{simplify}\mathrm{grouped}\mathrm{terms}\right)\hfill \\ \hfill x& =& 0÷\left(-7\right)\hfill \\ \hfill therefore\phantom{\rule{1.em}{0ex}}x& =& 0\phantom{\rule{1.em}{0ex}}\phantom{\rule{1.em}{0ex}}\phantom{\rule{1.em}{0ex}}\mathrm{zero}\mathrm{divided}\mathrm{by}\mathrm{any}\mathrm{number}\mathrm{is}0\hfill \end{array}$
4. Substitute solution into original equation:

$\begin{array}{ccc}\hfill \frac{2-\left(0\right)}{3\left(0\right)+1}& =& 2\hfill \\ \hfill \frac{2}{1}& =& 2\hfill \end{array}$

Since both sides are equal to 2, the answer is correct.

5. The solution of $\frac{2-x}{3x+1}=2$ is $x=0$ .

Solve for $x$ : $\frac{4}{3}x-6=7x+2$

1. We are given $\frac{4}{3}x-6=7x+2$ and are required to solve for $x$ .

2. We start with multiplying each of the terms in the equation by 3, then grouping like terms and then simplifying.

3. $\begin{array}{ccc}\hfill \frac{4}{3}x-6& =& 7x+2\hfill \\ \hfill 4x-18& =& 21x+6\phantom{\rule{1.em}{0ex}}\left(\mathrm{each}\mathrm{term}\mathrm{is}\mathrm{multiplied}\mathrm{by}3\right)\hfill \\ \hfill 4x-21x& =& 6+18\phantom{\rule{1.em}{0ex}}\left(\mathrm{move}\mathrm{all}\mathrm{terms}\mathrm{with}\mathrm{x}\mathrm{to}\mathrm{the}\mathrm{LHS}\hfill \\ \hfill \mathrm{and}\mathrm{all}\mathrm{constant}\mathrm{terms}\mathrm{to}\mathrm{the}\mathrm{RHS}\mathrm{of}\mathrm{the}=\right)\\ \hfill -17x& =& 24\phantom{\rule{1.em}{0ex}}\phantom{\rule{1.em}{0ex}}\phantom{\rule{1.em}{0ex}}\left(\mathrm{simplify}\mathrm{grouped}\mathrm{terms}\right)\hfill \\ \hfill \frac{-17}{-17}x& =& \frac{24}{-17}\phantom{\rule{1.em}{0ex}}\phantom{\rule{1.em}{0ex}}\left(\mathrm{divide}\mathrm{both}\mathrm{sides}\mathrm{by}-17\right)\hfill \\ \hfill x& =& \frac{-24}{17}\hfill \end{array}$
4. Substitute solution into original equation:

$\begin{array}{ccc}\hfill \frac{4}{3}×\frac{-24}{17}-6& =& 7×\frac{-24}{17}+2\hfill \\ \hfill \frac{4×\left(-8\right)}{\left(17\right)}-6& =& \frac{7×\left(-24\right)}{17}+2\hfill \\ \hfill \frac{\left(-32\right)}{17}-6& =& \frac{-168}{17}+2\hfill \\ \hfill \frac{-32-102}{17}& =& \frac{\left(-168\right)+34}{17}\hfill \\ \hfill \frac{-134}{17}& =& \frac{-134}{17}\hfill \end{array}$

Since both sides are equal to $\frac{-134}{17}$ , the answer is correct.

5. The solution of $\frac{4}{3}x-6=7x+2$ is,    $x=\frac{-24}{17}$ .

## Solving linear equations

1. Solve for $y$ : $2y-3=7$
2. Solve for $w$ : $-3w=0$
3. Solve for $z$ : $4z=16$
4. Solve for $t$ : $12t+0=144$
5. Solve for $x$ : $7+5x=62$
6. Solve for $y$ : $55=5y+\frac{3}{4}$
7. Solve for $z$ : $5z=3z+45$
8. Solve for $a$ : $23a-12=6+2a$
9. Solve for $b$ : $12-6b+34b=2b-24-64$
10. Solve for $c$ : $6c+3c=4-5\left(2c-3\right)$
11. Solve for $p$ : $18-2p=p+9$
12. Solve for $q$ : $\frac{4}{q}=\frac{16}{24}$
13. Solve for $q$ : $\frac{4}{1}=\frac{q}{2}$
14. Solve for $r$ : $-\left(-16-r\right)=13r-1$
15. Solve for $d$ : $6d-2+2d=-2+4d+8$
16. Solve for $f$ : $3f-10=10$
17. Solve for $v$ : $3v+16=4v-10$
18. Solve for $k$ : $10k+5+0=-2k+-3k+80$
19. Solve for $j$ : $8\left(j-4\right)=5\left(j-4\right)$
20. Solve for $m$ : $6=6\left(m+7\right)+5m$

what is demand
what is mean by unitary elastic demand
demand is said to be unitary elastic when the percentage change in the demand is equal to the percentage change in the price
George
what is the principle of equi-marginal utility
what is Economics and it important
what is production
Anita
what is Economic
what is the meaning of Economic
Anita
economics is a science which studies human behaviour as a relationship between ends and scarce means which have alternative uses
Boso
I don't know.
natchanan
u don't
Ssali
@ Boso thanks for the definition ✌
Raewyn
boso u r too much u try
Liambee
ya nyc
Ssali
Thanks kk
Anita
pls can I ask more questions
Anita
what is production
Anita
production is creation of goods and services
George
what is macroeconomics and microeconomics
Anita
macroeconomics deals with larger economic units such as GDP,GNP,employment while microeconomics deals with smaller economic units such firm and household
George
Thanks
Anita
Explain the ff Scarcity Ends Demand Supply Choice Scale of preference
Anita
macroeconomics deals with larger economic units such as GDP,GNP,employment while microeconomics deals with smaller economic units such firm and household
George
Gross Domestic product...it represent the total value of the products produced within the country including foreign industries
what is products
Anita
what are the favourable demand
list of climate that affect demands
Odia
What is two major forms of international trade?
What is Economics and why it is important
De ans,Economics is the study of women behavior as a relationship between end and scared mean which have alternative uses.
Anita
What is Inflation
More money = more consumers, more consumers = lessen the product, less product = high price, high price = inflation
TuroN
is it definition
Odia
why price and quantity increase
condition under which price and quantity will be increased at the same time
Otuu
factors that hinders mobility of labour
what is scarcity
why are people still unemployed in this economy we live in
why are people still unemployed in this economy
Joyce
Because of high technology
Innocent
Due to low government expenditure, the state does not have money to invest in new projects that can result in more job opportunities.
Young
good afternoon all, what are the examples of development projects Pls?
James
I 'm not together with him, when we say government expenditure mean there is recession for her economic country. That why many people still unemployed in this economy we live in, it mainly depend for two phases like Natural hazards and human activities.
Innocent
For the first answer I was responded we are concerns to intensive technology in the whole world it lead to reduce of many workers.
Innocent
wat does the abbreviation ppc mean?
Tumiso
I would like to give you ideas so that you get well how can give answer to this question dears. Attempt to know these words and what these means; Deficit, Surplus and Balanced budget.
Innocent
ppc mean pay -per-click known as search engine marketing
Innocent
i found it ppc means production possibility curve
Tumiso
in economic is that true according to your answer, however about of Marketing is that Pay Per Click.
Innocent
how is inflation, output gap relate to monetary policy
Got questions? Join the online conversation and get instant answers! By Richley Crapo By OpenStax By Steve Gibbs By Madison Christian By Brooke Delaney By Jessica Collett By Dakota Bocan By OpenStax By Brooke Delaney By Rohini Ajay